Primary Human Renal-Derived Tubular Epithelial Cells Fail to Recognize and Suppress BK Virus Infection. Issue 8 (August 2017) - de Kort, Hanneke; Heutinck, Kirstin M.; Ruben, Jurjen M.; Ede V. Silva, Alessa; Wolthers, Katja C.; Hamann, Jörg; ten Berge, Ineke J.M.
Abstract : Background: BK polyomavirus (BKV)–associated nephropathy is a threat to kidney allograft survival affecting up to 15% of renal transplant patients. Previous studies revealed that tubular epithelial cells (TEC) show a limited response towards BKV infection. Here we investigated the interplay between BKV and TEC in more detail. In particular, we questioned whether BKV suppresses and/or evades antiviral responses. Methods: Human primary TEC and peripheral blood mononuclear cells were infected with BKV Dunlop strain or other viruses. Moreover, TEC were stimulated with genomic double-stranded (ds)DNA or IFN. Viral replication and cellular responses were measured using quantitative real time PCR and multiplex assay. Results: BKV infection of primary human TEC did not induce an antiviral response, whereas infection with influenza A virus, herpes simplex virus 1, or cytomegalovirus induced a strong antiviral response measured by upregulation of interferon-stimulated genes, such as CXCL10 and DAI. In addition, intracellular delivery of dsDNA or stimulation with IFN did elicit a rapid and pronounced response. However, BKV infection did not affect dsDNA-induced gene expression, indicating BKV did not modulate the antiviral response. Prestimulation of primary TEC with IFNα or dsDNA did not hamper replication of BKV, whereas influenza and herpes simplex virus 1 replication were clearly reduced. In contrast, BKV infection of leukocytes did elicit an antiviral response. Conclusions: BKV specifically evades innate immunity in TEC and is not susceptible to an intrinsic interferon response, which may facilitate latent presence of the virus in this cell type. Abstract : de Kort et al describe the unique avoidance of BK polyomavirus at inducing antiviral responses in human primary tubular epithelial cells resulting in a cell-intrinsic failure to suppress BKV infection in vitro, which may explain its latent presence in vivo. Supplemental digital content is available in the text.